The merits of universal scholarships: Benefit-cost evidence from the Kalamazoo promise - Timothy J. Bartik; Brad J. Hershbein; Marta Lachowska (W.E. Upjohn Institute for Employment Research, 2016)
As the costs of higher education rise, many communities have begun to adopt their own financial aid strategy: place-based scholarships for students graduating from the local school district. Some place-based scholarships impose merit- and/or need-based restrictions, while others require little more than residency and graduation. In this paper, we examine the reach and cost-effectiveness of the Kalamazoo Promise, one of the more universal and more generous place-based scholarships. Building upon estimates of the program's heterogeneous effects on degree attainment, individual-level scholarship cost data, and projections of future earning profiles by education, we examine the Promise's benefit-cost ratios for different types of students differentiated by income, race, and gender. Although the average break-even rate of return of the program is about 11 percent, rates of return vary greatly by group. The Promise has high returns for both low-income and non-low-income groups, for nonwhites, and for women, while benefit assumptions matter more for whites and men. Our results show that universal scholarships can reach many students and have a high rate of return, particularly for places with a high percentage of African American students.
Keywords: I21; I22; I24; 330; place-based scholarship; enrollment; college completion; natural experiment; difference-in-differences; financial aid policy; benefit-cost analysis